INFLUENCE OF INSTRUCTIONAL RESOURCES ON QUALITY OF EDUCATION IN PUBLIC SECONDARY SCHOOLS IN MURANG'A COUNTY, KENYA - Mwaniki, Wilson; Ogola , Martin; Nyerere, Jackline (African Journal of Education and Practice, 2022)
Statement of the Research Problem: Instructional resources play an important role in supplementing teachers' classroom pedagogy and thus realization of quality education in public secondary schools. However, in Murang'a County, many public secondary schools registering a low quality of education. Purpose of the Study: This study aimed at assessing the influence of instructional resources on quality of education in public secondary schools in Murang'a County, Kenya. Methodology: The study adopted a correlation research design. This study targeted 292 principals and 3206 teachers totaling 3498 from which a sample of 360 respondents (10.3%) was determined using Yamane's Formula. Using stratified sampling, eight strata considering sub-counties were created. From every sub-county, three principals were selected using purposive sampling. However, from each sub-county, 42 teachers (14 teachers per school) were selected using simple random sampling to avoid bias. Questionnaires were used to gather information from principals and teachers whereas a documentary checklist guide was used by the researcher. Quantitative data were analyzed using descriptive statistics such as frequencies and percentages and inferentially using Pearson's Product Moment Correlation Analysis with the help of Statistical Packages for Social Sciences (SPSS 23) and presented by using tables. Research Findings: The study established that students' academic performance in national examinations (KCSE) is low, students' completion rates with quality grades (C+ and above) are on a decreasing trend and levels and frequency of participation in co-curricular activities are low. From the study, despite the efforts by the government and other stakeholders in secondary education, levels of provision of instructional resources, facilities and teaching staff are still low, which has compromised the quality of secondary education. Unique Contribution to Theory, Policy and Practice: This study affirms the theoretical perspectives of the Education Production Function Theory since it revealed that there is a correlation between instruction resources and quality of education. Thus, as a practice, teachers should constantly utilize variety of instructional resources owing to their contribution to the quality of teaching offered to students. As a policy, the government should enforce full implementation of adequate provision of instructional resources as a solution to low levels of educational quality in public secondary schools.